2016
DOI: 10.1016/j.parkreldis.2016.06.011
|View full text |Cite|
|
Sign up to set email alerts
|

Impaired eye blink classical conditioning distinguishes dystonic patients with and without tremor

Abstract: The present data show that cerebellar impairment segregates with the presence of tremor in patients with dystonia, suggesting that the cerebellum might have a role in the occurrence of dystonic tremor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 16 publications
4
43
1
Order By: Relevance
“…Several studies have found normal cerebellar function or connectivity in idiopathic cervical dystonia patients, or abnormal cerebellar function only in cervical dystonia patients with tremor (Delnooz et al, 2013;Sadnicka et al, 2014;Antelmi et al, 2016;Bologna et al, 2016;Avanzino et al, 2018). Here, we found that all lesions causing cervical dystonia were connected to the cerebellum, including cases with no head tremor ( Supplementary Fig.…”
Section: The Cerebellum In Cervical Dystoniasupporting
confidence: 60%
“…Several studies have found normal cerebellar function or connectivity in idiopathic cervical dystonia patients, or abnormal cerebellar function only in cervical dystonia patients with tremor (Delnooz et al, 2013;Sadnicka et al, 2014;Antelmi et al, 2016;Bologna et al, 2016;Avanzino et al, 2018). Here, we found that all lesions causing cervical dystonia were connected to the cerebellum, including cases with no head tremor ( Supplementary Fig.…”
Section: The Cerebellum In Cervical Dystoniasupporting
confidence: 60%
“…It is therefore possible that proprioceptive afferent information flowing from the cerebellum in CD and FHD competes, once it reaches the thalamus, with tactile information during index finger movements, thereby altering the timing of tactile sensory processing gating. Concordantly recent evidence suggests a role of the cerebellum in the pathophysiological mechanisms of dystonia . The observation that movement velocity in patients with CD and FHD did not vary during the sensorimotor integration task suggests that there might be an unbalanced interplay in these patients between motor and sensory information in favor of motor output, with an excessive degree of gating on tactile information.…”
Section: Discussionmentioning
confidence: 62%
“…Concordantly recent evidence suggests a role of the cerebellum in the pathophysiological mechanisms of dystonia. [42][43][44][45] The observation that movement velocity in patients with CD and FHD did not vary during the sensorimotor integration task suggests that there might be an unbalanced interplay in these patients between motor and sensory information in favor of motor output, with an excessive degree of gating on tactile information. As tactile information gating may promote movement arrest, excessive tactile gating may reduce the likelihood of the movement ceasing.…”
Section: Discussionmentioning
confidence: 98%
“…Data show that cerebellar impairment segregates with the presence of tremor in patients with dystonia, thus suggesting that the cerebellum might play a specific role in the occurrence of dystonic tremor [102]. …”
Section: Reviewmentioning
confidence: 99%